MASALAH -MASALAH YANG DIALAMI SISWA/SISWI SMK TEKNOLOGI KECAMATAN SIAK HULU TAHUN 2015 / 2016 - Asyari, Abu Asyari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The study is aimed at: 1) finding out problems experienced by the male students of Teknologi Vocational High School of Siak Hulu Sub District dealing with personality, emotional, learning, familial and social aspects; 2) finding out problems experienced by the female students of Teknologi Vocational High School of Siak Hulu Sub District dealing with personality, emotional, learning, familial and social aspects; 3) finding out problems experienced by the male and female students of Teknologi Vocational High School of Siak Hulu Sub District dealing with personality, emotional, learning, familial and social aspects. The data were collected by using questionnaire. The subjects of the research are 200 students of Teknologi Vocational High School of Siak Hulu Sub District in 2015. The sampling technique is the total one. It means that the entire population were taken as sample, therefore there are 200 samples in the research. The research results showed that the problems experienced by the male and female students of Teknologi Vocational High School of Siak Hulu Sub District are generally categorized moderate that is amounted to 56%. Then, 44% of them are categorized low and 0% is high. The problem factors of male and female students can be generally seen from the results of studentsâ answers to the questionnaire of which their highest score are about item no.6 namely most of them felt that they are the best in the class.Keywords: problems